Correction the functional state of students of 19-20 years old by facilities of the standard training (on the example of swimming). - Glushchenko N.V; Malikov N.V (Kharkov National Pedagogical University, 2010)
The features of the functional state of students are presented at the beginning of systematic employments standard swimming. In research took part 70 students in the age of 19-20. The results of experimental research of efficiency of application of the author program are presented. The dynamics of changes of basic indexes of the functional state of youths is analysed. It is set that application of the standard loading in a water environment is capable effectively and safe-health to promote the level of the functional state of students.